Vector valued martingale-ergodic and ergodic-martingale theorems - Shahidi, Farruh; Ganiev, Inomjon (Taylor& Francis group, LLC, 2012)
We prove martingale-ergodic and ergodic-martingale theorems for vector-valued Bochner integrable functions. We obtain dominant and maximal inequalities. We also prove weighted and multiparameter martingale-ergodic and ergodic-martingale theorems